Corrigendum to “Fate and transport of viruses, bacteria and antimicrobial resistance associated with wet wipes and microplastics through wastewater treatment to coastal waters” [Water Research (2026) /126281] - Jessica L. Kevill; Margaret E. Knight; Yashi Jain; Karina A. Marsden; Rachel C. Williams; Kate Herridge; Winnie Courtene-Jones; Peter Robins; Shelagh K. Malham; Davey L. Jones (Water Research, 2026)

Fate and transport of viruses, bacteria and antimicrobial resistance associated with wet wipes and microplastics through wastewater treatment to coastal waters - Jessica L. Kevill; Margaret E. Knight; Yashi Jain; Karina A. Marsden; Rachel C. Williams; Kate Herridge; Winnie Courtene-Jones; Peter Robins; Shelagh K. Malham; Davey L. Jones (Water Research, 2026)

Comparative impact of sunlight and salinity on human pathogenic virus survival in river, estuarine, and marine water microcosms - Jessica L. Kevill; Kate Herridge; Xiaorong Li; Kata Farkas; Shelagh K. Malham; Peter Robins; Davey L. Jones (Water Research, 2025)

Evaluation of Three Viral Capsid Integrity qPCR Methods for Wastewater-Based Viral Surveillance - Jessica L. Kevill; Kata Farkas; Kate Herridge; Shelagh K. Malham; Davey L. Jones (Food and Environmental Virology, 2025)
Capsid Integrity qPCR (CI-qPCR) assays offer a promising alternative to cell culture-based infectivity assays for assessing pathogenic human virus viability in wastewater. This study compared three CI-qPCR methods: two novel (Crosslinker, TruTiter) and one established (PMAxx dye). These methods were evaluated on heat-inactivated and non-heat-inactivated ‘live’ viruses spiked into phosphate-buffered saline ( PBS) and wastewater, as well as on viruses naturally present in wastewater samples. The viral panel included Human adenovirus 5 (HAdV), enterovirus A71 (EV), hepatitis-A virus (HAV), influenza-A H3N2 (IAV), respiratory syncytial virus A2 (RSV), norovirus GI, norovirus GII, and SARS-CoV-2. All three methods successfully differentiated between degraded, heat-inactivated, and live viruses in PBS. While all three methods were comparable for HAdV and norovirus GI, PMAxx detected significantly lower gene copies for EV and IAV. In spiked wastewater, PMAxx yielded significantly lower gene copies for all heat-inactivated viruses (HAdV, EV, HAV, IAV, and RSV) compared to the Crosslinker and TruTiter methods. For viruses naturally present in wastewater (un-spiked), no significant difference was observed between PMAxx and TruTiter methods. Intact, potentially infectious viruses were detected using both PMAxx and TruTiter on untreated and treated wastewater samples. A comparative analysis of qPCR data and TEM images revealed that viral flocculation of IAV may interfere with capsid integrity assays using intercalating dyes. In summary, our findings not only advance the development of more effective methods for assessing viral viability in wastewater, but also highlight the potential of CI-qPCR techniques to enhance early warning systems for emerging pathogens, thereby strengthening public health preparedness and response strategies.

Microcosm experiment investigating climate-induced thermal effects on human virus viability in seawater: qPCR vs capsid integrity for enhanced risk management - Jessica L. Kevill; Xiaorong Li; Alvaro Garcia-Delgado; Kate Herridge; Kata Farkas; William Gaze; Peter Robins; Shelagh K. Malham; Davey L. Jones (Marine Pollution Bulletin, 2024)